Ethiopia–China Economic Relations: A Classic Win–Win Situation?. (1st July 2016) - ,
Abstract : A significant body of literature has held that Chinese interest in Africa is driven by a hunger for resources. This makes Ethiopia an important case study. Ethiopia experienced high rates of economic growth from 2003 onwards, thanks to rapid agricultural development. This period was also characterized by an intensification of Ethiopia–China relations. Bilateral trade between the two countries expanded rapidly, and China is currently the country's top trading partner. Ethiopia gained from China's zero-tariff policy on agricultural imports, and there was a dramatic growth in its sesame exports to China. China is also a major source of manufactured goods and machinery for Ethiopia. Despite being an agricultural exporter, it has attracted significant volumes of Chinese official financial flows and foreign direct investment (FDI). Chinese official finance is directed to building infrastructure, whereas Chinese FDI is directed to the manufacturing sector. This article concludes that the overall impact of China on Ethiopia is beneficial.